Indirect competitive enzyme-linked immunosorbent assay (ELISA) for the determination of mammalian gelatin in pharmaceutical capsules - Tukiran, Nur Azira; Ismail, Amin; Mustafa, Shuhaimi; Hamid, Muhajir (Springer, 2018)
Gelatin is derived from partial hydrolysis of type I collagen (connective tissues such as skin, bone, tendon, and ligament), which is commonly obtained from mammalian sources (porcine and bovine). However, the use of gelatin derived from mammalian sources in pharmaceutical products have become a controversial issue regarding religious and health concern. Thus, the aim of this study was to develop indirect competitive enzyme-linked immunosorbent assays (ELISAs) based on antipeptide polyclonal antibodies (pAbs) for the determination of mammalian gelatin in pharmaceutical capsules. Polyclonal antibodies against amino acid sequences of collagen α2 (I) chain were used (pAb1 and pAb2). The IC50 value of 0.390 µg/mL and detection limit of 0.082 µg/mL (in buffer) were achieved by ELISA based on pAb2. The intra-assay (<14%) and inter-assay (<13%) coefficients of variation were also acceptable. The ELISA was successfully applied for the determination of mammalian gelatin in pharmaceutical capsule (hard shell capsule, soft shell capsule, and tablet). The result suggests that this ELISA method is useful for determination of mammalian gelatin in selected pharmaceutical capsules.